Transforming Secondary Education in Bangladesh: A Reflective Essay on ‎student-centered Pedagogy - Chakraborty, Suhash Chandra; Akanda , Md. Romzan Ali; Haque , Md Tozammel (SPC Journal of Education, 2025)
The reflective essay tries to find out the necessity of student-based instructional pedagogy in the ‎context of Bangladesh Secondary Education system. The data and information have been collected through library methods, i.e., from various sources such as books, journals, government websites, newspapers, etc. The data reflects the findings that most of the teachers follow the ‎traditional teacher-based teaching method while conducting classes in secondary schools. The reasons for this are numerous, including the use of traditional methods, inadequate professional development training, flawed curriculum systems, a lack of technological knowledge, and an authoritative attitude. Conversely, secondary education needs a democratic ‎classroom where students will get their proper involvement with belongingness, and their voice ‎will be heard. The authorities have taken some steps, but they also face challenges in implementing a ‎student-based teaching system. Teachers also face other challenges like large classroom size, ‎accommodation problems, and overworkload, which tend to encourage them to follow ‎teacher-based classroom activities‎.